ORIGAMI SOMA CUBE: MEDIA PEMBELAJARAN GEOMETRI UNTUK MENDUKUNG KECERDASAN MATEMATIKA SPASIAL SISWA - Muhamad Toyib; Alviani Milenia Safitri; Nuqthy Faiziyah (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Geometry instruction can help you build spatial intelligence. Numerous studies have produced instructional materials to enhance spatial intelligence in geometry learning. However, there hasn't been enough research done on student-friendly media, particularly game-based media, thus it still has to be developed. In order to promote students' mathematical spatial intelligence, this study uses Origatrid learning resources to teach geometry. Using the idea of the origami soma cube in educational media. The study employed a research and development (R&D) model, and the sign test was used to gauge its efficacy. 20 eighth grader students participated in the study at SMP 1 Pakuhaji in Tangerang Regency. Experts in media and learning materials conducted tests on Origatrid, and they concluded that it might be used for educational purposes. Additionally, after the hypothesis was tested, scores before and after utilizing Origatrid as a learning tool showed differences.